1998
DOI: 10.1111/j.1468-0351.1998.tb00053.x
|View full text |Cite
|
Sign up to set email alerts
|

Foreign direct investment in Russia's regions 1993‐95. Why so little and where has it gone?

Abstract: In this paper, foreign direct investment (FDI) into Russia's regions during the period 1993-95 is analysed using recently available regional data. Russia's regions are shown to be much richer than China's, but much poorer than US states, though with far less FDI than either country. FDI into the regions is also low compared to both Western and Eastern European countries, but has grown substantially from very low levels. Relatively higher FDI is found to occur when crime is lower, market size is bigger and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
41
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(45 citation statements)
references
References 8 publications
(8 reference statements)
2
41
1
1
Order By: Relevance
“…Some studies have confirmed that crime hinders investment in several countries. Brock (1998) finds that relatively higher FDI is attracted to the regions of Russia where the level of crime is lower. Another study by Madrazo-Rojas (2009) finds that violent organized crime has a negative impact on FDI in Mexican states.…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have confirmed that crime hinders investment in several countries. Brock (1998) finds that relatively higher FDI is attracted to the regions of Russia where the level of crime is lower. Another study by Madrazo-Rojas (2009) finds that violent organized crime has a negative impact on FDI in Mexican states.…”
Section: Introductionmentioning
confidence: 99%
“…2 'Destiny' and 'opportunity' in FDI GeoJournal (2007) 70:195-211 205 EU countries in Eastern Europe); and cultural affinity between investors and host regions (e.g. for Hong Kong and Macao in the Pearl River Delta, or for Japanese and others in Canada) (Hamilton and Carter 2005;Sit 1991Sit , 1993Wu and Radbone 2005;Deichmann 2000;Brock 1998;Hines 1996;Duo et al 2000;Mai 2002;Wei 1995;Berger 2002;Wu 2000;Harvey 1989a;Yeh and Xu 1996;Fuchs and Pernia 1987;Coughlin et al 1991;Syamwil and Tanimura 2000;Hong 1996;Krongkaew 1996;Ó hUallacháin 1985;Basile 2004;Edgington 1984). The order of importance among these factors may change from region to region, and often the location of cheap labor does not coincide with the capital city or other large cities.…”
Section: Foreign Direct Investment (Fdi)mentioning
confidence: 98%
“…The local or regional 'pull' effects for FDI are to some degree idiosyncratic, (e.g. low local crime rates in Russia (Brock 1998)), but more generally there are several local pull-effects in host countries worldwide, whether developed or developing, in what seems to constitute a 'destiny' for regions or cities. Basically these effects are similar to investment preferences by domestic investors (Glickman and Woodward 1988): preference for capital or big cities and their large markets; ample and enhanced financial and cultural services; skilled human resources; government concentration; cheap labor; transportation infrastructure; regional tax incentives; nearness to investing countries if relevant (e.g.…”
Section: Foreign Direct Investment (Fdi)mentioning
confidence: 99%
“…The majority of empirical papers reports positive effects associated with regional market size in Russia (see e.g. Brock, 1998;Broadman and Recanatini, 2001;Iwasaki and Suganuma, 2005;Ledyaeva and Linden, 2006;Kayam, Hisarciklilar, and Yabrukov, 2007;Ledyaeva, 2009). Conversely, Manaenkov (2000) reports that market size is irrelevant for the decision of FDI to enter into a region, finding that the gravitation model is not robust and that regional size heightens the attractiveness for FDI only if the sample includes Moscow.…”
Section: Market Size As a Determinant Of Fdi Locationmentioning
confidence: 99%